“Five Plus Two” skills set and success of young art entrepreneurs : a case study of seven visual artists / Dr Abdul Rahim Said - Abdul Rahim, Said (Universiti Teknologi MARA, Perak, 2018)
This article aims at showcasing the design, development and implementation of a Young Art Entrepreneurs (YAE) career development scheme for visual artists, based on a model of “five plus two” entrepreneurial skills sets, advanced by Marco Thom (2016). It documents the philosophy, approach and methodology to develop entrepreneurship skills amongst seven young graduate artists over a period of six months. Findings based on an analysis of seven case studies of individual artists involved in the First Cohort of YAE in 2017, indicate that those who are able to better internalize the “five plus two” skill sets, seem to show a greater chance of success in launching and managing their own art enterprises.